IMPLEMENTASI SNAKE AND LADDER GAME MENGGUNAKAN PENDEKATAN TARL (TEACHING AT THE RIGHT LEVEL) UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI MATERI GETARAN KELAS VIII - Cica Adelia Permatasari; Agung Mulyo Setiawan; Sitti Djuwarijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a Classroom Action Research (PTK) which aims to improve the collaboration skills of class VIII students by implementing snake and ladder game using approach Teaching at the Right Level (TaRL). The problem raised from this research is the low collaboration skills of students during the group learning process, especially in science subjects. The research method used is one cycle PTK with qualitative data analysis from the results of observations and questionnaires. The research subjects used were 28 class VIII D students of SMPN 2 Pakis Malang Regency who were grouped based on their level of cognitive ability. The results obtained from this research show that collaboration skills have improved with its implementation snake and ladder game using the TaRL approach, namely the good category for indicators of mutual assistance, while the improvement with the very good category is for indicators of communication, division of tasks, decision making, respect for opinions and responsibility. Thus, students in this learning activity can improve collaboration skills and build a positive work culture within the group.